PENGEMBANGAN MODUL DIGITAL MATEMATIKA MATERI ARITMATIKA SOSIAL BERBASIS CASE METHOD UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Arni, Sarah; Halida, Halida; Wartiningsih, Agus (Jurnal Visi Ilmu Pendidikan, 2025)
Abstract This study aims to develop a digital module based on the case method for social arithmetic material to enhance elementary school students' problem-solving skills and learning outcomes. The research employed Research and Development (R&D) methodology utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The module was designed as an interactive and contextual learning resource, presenting authentic cases as learning stimuli. Literature review indicates the effectiveness of case-based learning and digital technology integration in mathematics education. Validation results from media, material, and language experts demonstrated that the module achieved very valid and highly practical criteria with an aggregate validity score of 93.5% and practicality score of 90.5%. Implementation trials on elementary school students revealed significant improvement in problem-solving abilities across Polya's four phases (78.56% achievement in experimental class versus 56.25% in control class) and learning outcomes with N-Gain of 0.68 (moderate category) and Cohen's d effect size of 1.23 (strong effect), statistically significant at p = 0.001. The digital module effectively bridges the gap between theoretical mathematical concepts and real-world application through contextual transaction scenarios, facilitating meaningful knowledge construction and metacognitive competency development essential for 21st-century mathematics learning. Keywords: Digital Module, Case Method, Problem Solving, Social Arithmetic, Elementary Mathematics. Abstrak Penelitian ini bertujuan mengembangkan modul digital berbasis case method pada materi aritmetika sosial untuk meningkatkan kemampuan pemecahan masalah dan hasil belajar siswa sekolah dasar. Metode penelitian menggunakan Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Modul dirancang secara interaktif dan kontekstual dengan menampilkan kasus transaksi ekonomi autentik sebagai stimulus pembelajaran. Kajian literatur mengonfirmasi efektivitas pembelajaran berbasis kasus dan integrasi teknologi digital dalam pendidikan matematika. Hasil validasi ahli materi, media, dan bahasa menunjukkan modul mencapai kategori sangat valid dengan skor agregat 93,5% dan sangat praktis dengan skor 90,5%. Uji coba implementasi pada siswa SD menunjukkan peningkatan signifikan pada kemampuan problem solving lintas empat fase Polya (capaian 78,56% kelas eksperimen dibandingkan 56,25% kelas kontrol) dan hasil belajar dengan N-Gain 0,68 (kategori sedang) serta effect size Cohen's d = 1,23 (strong effect), signifikan secara statistik pada p = 0,001. Modul digital ini efektif menjembatani kesenjangan antara konsep matematika teoretis dengan aplikasi dunia nyata melalui skenario kontekstual, memfasilitasi konstruksi pengetahuan bermakna dan pengembangan kompetensi metakognitif esensial untuk pembelajaran matematika abad ke-21.